PERAN OPINI AUDIT SEBAGAI PEMODERASI PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL, DAN KOMITE AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Fadhli Azhari; Muhammad Nuryatno (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
The purpose of this research is to find the role of audit opinion as a moderator of the affect of profitability, firm size, institutional ownership, and audit committee to the timeliness of financial reporting on manufacturing companies listed on the Indonesia Stock Exchange period 2012 to 2016. The population of this research are 133 companies. Sampling method that used in this research is purposive sampling, so that obtained 96 sample companies for 5 years observation (2012 – 2016) with 480 analysis unit. Analysis data technique that used in this research is descriptive statistics analysis dan inferencial statistics analysis with logistic regression method. The hypothesis testing showed that (1) profitability positively affects the timeliness of financial reporting, (2) firm size positively affects the timeliness of financial reporting, (3) institutional ownership does not affect the timeliness of financial reporting, (4) audit committee does not affect the timeliness of financial reporting, (5) audit opinion can not moderate the affect of profitability to the timeliness of financial reporting, (6) audit opinion can not moderate the affect of firm size to the timeliness of financial reporting, (7) audit opinion can not moderate the affect of institutional ownership to the timeliness of financial reporting, (8) audit opinion can not moderate the affect of audit committee to the timeliness of financial reporting.